Analisis Waktu Perjalanan Terhadap Pembukaan Jalur Lingkar Selatan Surakarta Menggunakan Program TFTP - Suwardi, Suwardi (Semesta Teknika, 2008)
Surakarta road network services high traffic volume to/from Surakarta city. It is caused by the activities are still centered. In addition, outside road network of city which is provided for traffic only passing Surakarta city is not available yet. Therefore, a Surakarta road network needs urgently to be expanded and a proposed ring-road is considered necessary. In order to anticipate the future traffic condition, effects of a proposed ring-road is studied. The aim of study is to predict the future traffic condition in terms of effective journey time after a proposed ring-road is implemented using Teacher Friendly Transportation Program (TFTP). The results show that effective journey time in 2009 and 2014 was significantly reduced after opening the proposed ring-road in the Surakarta road networks. The efficiency of journey time in 2009 was predicted in the range of 8 to 9 minutes for three alternatives and in 2014 was about 9 to 11 minutes. Meanwhile, the journey time for ring-road in 2009 was estimated in 17.1 minutes with the efficiency of journey time for alternative 1, 2 and 3 was calculated in 17.9, 10.9 and 13.9 minutes, respectively. The journey time for ring-road in 2014 was found to be 19 minutes with the efficiency of journey time for alternative 1, 2 and 3 is 20, 17.5 and 15, respectively. Â